2021
DOI: 10.1016/j.jtumed.2020.12.011
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of the superior vena cava obstruction in a 16-year-old boy with Burkitt's lymphoma: A case report

Abstract: Burkitt's lymphoma (BL) is an aggressive non-Hodgkin B-cell lymphoma. Superior vena cava obstruction (SVCO) is considered a rare presentation of BL and it is usually associated with other types of non-Hodgkin lymphoma such as diffuse large-cell. We report a rare case of sporadic BL with SVCO in a 16-year-old boy with nasopharyngeal, mediastinal, and adrenal masses. The patient presented with a two-month history of left upper neck swelling that increased with time and was not associated with other symptoms. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Last but not least, it is worth mentioning that most studies included in our review have reported to alter the intensity and regimen of anticancer treatment in blood cancer children during course of SARS-CoV-2 infection, however, many studies have reported to successfully treat COVID-19 in blood cancer children by proceeding with no changes to the anticancer treatment (13,23,25,31,32,38,57,58,63,64,76,78,81,87,90,105,115,117,118,128,156,157). Management of COVID-19 in children with blood cancer is limited and guidelines were largely based on adult data.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, it is worth mentioning that most studies included in our review have reported to alter the intensity and regimen of anticancer treatment in blood cancer children during course of SARS-CoV-2 infection, however, many studies have reported to successfully treat COVID-19 in blood cancer children by proceeding with no changes to the anticancer treatment (13,23,25,31,32,38,57,58,63,64,76,78,81,87,90,105,115,117,118,128,156,157). Management of COVID-19 in children with blood cancer is limited and guidelines were largely based on adult data.…”
Section: Discussionmentioning
confidence: 99%